2017
DOI: 10.1080/17435390.2017.1306129
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cytokine–IDO1–AhR loop in zinc oxide nanoparticle-induced acute pulmonary inflammation

Abstract: Zinc oxide nanoparticles (ZnONPs) are widely used in our daily life, such as in sunscreens and electronic nanodevices. However, pulmonary exposure to ZnONPs causes acute pulmonary inflammation, which is considered as an initial event for various respiratory diseases. Thus, elucidation of the underlying cellular mechanisms of ZnONPs can help us in predicting their potential effects in respiratory diseases. In this study, we observed that ZnONPs increased proinflammatory cytokines, accompanied with an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Their lungs were lavaged with 1mL saline and the recovered amount of lavagate was recorded and stored. The total cell count and cell type distribution in BALF were determined as previously described . Protein concentrations of BALF were measured using the Bradford assay (Bio‐Rad, Hercules, California).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their lungs were lavaged with 1mL saline and the recovered amount of lavagate was recorded and stored. The total cell count and cell type distribution in BALF were determined as previously described . Protein concentrations of BALF were measured using the Bradford assay (Bio‐Rad, Hercules, California).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue processing was followed by dehydration, clearing, and embedding. Hematoxylin and eosin staining was used for general histopathological examinations as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that AhR is not only involved in metabolizing toxicants but may also be involved in the pulmonary immune and pro-inflammatory responses [ 124 ]. For example, a study using AhR KO mice exposed to ZnONPs via oropharyngeal aspiration ( Table 3 ) showed that these mice had reduced cell numbers, total protein, LDH activity, and pro-inflammatory cytokine production in BALF compared to the wild type mice [ 125 ]. No increase in CYP1A1, a downstream target of AhR, was detected in AhR KO mice [ 125 ].…”
Section: Deficiency In Cell Signaling Molecules As Determinants Ofmentioning
confidence: 99%
“…For example, a study using AhR KO mice exposed to ZnONPs via oropharyngeal aspiration ( Table 3 ) showed that these mice had reduced cell numbers, total protein, LDH activity, and pro-inflammatory cytokine production in BALF compared to the wild type mice [ 125 ]. No increase in CYP1A1, a downstream target of AhR, was detected in AhR KO mice [ 125 ]. In addition, AhR KO mice did not display an increase in kynurenine (KYN), which is an endogenous AhR agonist [ 125 ].…”
Section: Deficiency In Cell Signaling Molecules As Determinants Ofmentioning
confidence: 99%